Prevention and control of COVID-19 in public transportation: Experience from China. (November 2020) - Shen, Jin; Duan, Hongyang; Zhang, Baoying; Wang, Jiaqi; Ji, John S.; Wang, Jiao; Pan, Lijun; Wang, Xianliang; Zhao, Kangfeng; Ying, Bo; Tang, Song; Zhang, Jian; et al.
Abstract: Due to continuous spread of coronavirus disease 2019 (COVID-19) worldwide, long-term effective prevention and control measures should be adopted for public transport facilities, as they are increasing in popularity and serve as the principal modes for travel of many people. The human infection risk could be extremely high due to length of exposure time window, transmission routes and structural characteristics during travel or work. This can result in the rapid spread of the infection. Based on the transmission characteristics of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and the nature of public transport sites, we identified comprehensive countermeasures toward the prevention and control of COVID-19, including the strengthening of personnel management, personal protection, environmental cleaning and disinfection, and health education. Multi-pronged strategies can enhance safety of public transportation. The prevention and control of the disease during the use of public transportation will be particularly important when all countries in the world resume production. The aim of this study is to introduce experience of the prevention and control measures for public transportation in China to promote the global response to COVID-19. Graphical abstract: Image 1 Highlights: Comprehensive countermeasures have been identified, including: strengthening personnel management, personal protection, environmental cleaning and disinfection, health education. Multi-pronged strategies can enhance safety during public transportation. Experience of the prevention and control measures for public transportation in China have been reviewed.